Studi Potensi Penggunaan Daun Mengkudu (Morinda citrifolia L.) sebagai Bahan Antibakteri Escherichia coli dan Salmonella typhimurium - Hafni Halimah; Dwi Margi Suci; Indah Wijayanti (Jurnal Ilmu Pertanian Indonesia, 2019)
The aim of this study was to evaluate the potential use of Noni (Morinda citrifolia L.) leaves as an antibacterial agent for Escherichia coli and Salmonella typhimurium. Noni leaves are processed with four methods i.e., mealing, blending, juicing, and decocting. The data obtained were analyzed descriptively. The variables measured were phytochemical analysis and antibacterial activity through bacterial inhibitory test. Qualitative test was used for phytochemical analysis and quantitative analysis was used for antibacterial of noni leaves. The antibacterial activity of noni leaves with diffusion well method used 4 concentrations i.e., 2.5; 5; 7.5; and 10% and extracted by maceration with 4 solvents i.e., water, ethanol, ethyl acetate, and hexane. The results showed that the processing of Noni leaves produced various active compounds. The noni leaves meal produces a more active type of compound group compared to 3 other treatments. Antibacterial tests against Escherichia coli were not seen in all noni leaves processing, but were seen to positively inhibit Salmonella typhimurium in the extraction process of Noni leaves meal using ethanol and ethyl acetate solvents at 48 hours maceration. The conclusions of the results showed that noni leaves meal extract using ethanol and ethyl acetate macerated for 48 hours was able to inhibit Salmonella typhimurium bacteria.